2022
DOI: 10.3390/polym14183856
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Solvent Hydrophilicity on the Enzymatic Ring-Opening Polymerization of L-Lactide by Candida rugosa Lipase

Abstract: Contradictions have been reported on the effect of organic solvents, especially toluene, on enzymatic ring-opening polymerization (eROP) of L-lactide. Studies have shown that log P, a common measure of hydrophilicity, affects enzyme activity. This study examines the effect of solvents with various log P values on the eROP of L-lactide, performed using Candida rugosa lipase (CRL). N,N-dimethylacetamide (DMA), 1,2-dimethoxybenzene, 1,4-dimethoxybenzene, diphenyl ether, and dodecane were used as the organic solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…A high Log P value indicates that a molecule is more non-polar and has a high ability to penetrate the lipid bilayer [23]. However, a high Log P value indicated that the molecule is difficult to dissolve in water because it is more non-polar or hydrophobic [25]. The hydrophobic nature is related to the ability of the drug to penetrate the lipid bilayer.…”
Section: Resultsmentioning
confidence: 99%
“…A high Log P value indicates that a molecule is more non-polar and has a high ability to penetrate the lipid bilayer [23]. However, a high Log P value indicated that the molecule is difficult to dissolve in water because it is more non-polar or hydrophobic [25]. The hydrophobic nature is related to the ability of the drug to penetrate the lipid bilayer.…”
Section: Resultsmentioning
confidence: 99%
“…A copolymer with an Mn of 3100 g/mol was obtained after 14 days at a reaction temperature of 80 °C. Curie et al [ 179 ] measured the effects of six organic solvents and ILs (1-butyl-3-methyl-imidazolium hexafluorophosphate, [BMIM][PF6]) on eROP. The results have shown that the highest molecular weight and conversion were obtained in the ionic liquid [BMIM][PF6], which were 3108 g/mol of Mn and 93.2%, respectively.…”
Section: Solvent System For Enzyme-catalyzed Synthesis Of Polyestersmentioning
confidence: 99%